MASS MEDIA INFLUENCE ON VOTING PATTERNS IN RURAL AREAS OF NIGERIA - Olumide , Adewale Adebayo; Obi, Chiamaka Ngozi (International Research Journal of Arts and Communication, 2025)
Political survival and democratic process are dependent on how well the citizens are informed, enlightened and mobilized. Mass information, in a democracy, is a necessity. As a result, the roles of mass media as harbingers of information, education and providers of entertainment become indispensable. However, the mass media of mass communication have failed in their effort to provide the traditional social responsibility functions with which they have been identified for ages, especially in the rural areas of Nigeria. The rural dwellers in Nigeria are not adequately informed about the political process and development like their urban counterparts. Many newsworthy events, which should be reported by the media, are not given attention in the rural areas. Radio, which is the favourite and the most loved among the rural dwellers, has not also done enough to orientate, re-orientate, educate, enlighten, and mobilize the rural areas. This is because most programmes done on radio are elitist and are carved in a foreign language-English-which most rural dwellers do not find easy to comprehend. Programmes about agriculture which concern the rural dwellers, if done at all, are aired in English Language. The study is driven by agenda-setting theory and two stepflow of information theory. The agenda setting theory posits that the media think for the audience by disseminating information which they think is important. The two step-flow of information theory states that some individual have better access to the media than others in the society. These people are called opinion leaders, while the others who have less access to the media of communication are called opinion-followers. The study recommends the establishment of community radio station in rural areas for political mobilization and information